The revolution in retailing: From market driven to market driving - KUMAR, Nirmalya (Institutional Knowledge at Singapore Management University, 1997)
The first image aroused by 'retailing' for many of us, especially those of us who are somewhat older, is that of the corner grocery store. Not so long agb retailing was, and it still is in some parts of the world, a fragmented, local, unsophisticated, traditional business run by vulnerable owner-operators. Yet, here we are talking about a revolution in retailing. Why? What has changed? Fundamentally retailers have grown up over the past 25 years into large, global, technology-intensive, powerful, fast-growth corporations managing their own brands. Several retailers have become the darlings of their stock markets. Hennes and Mauritz, the specialty clothing retailer, has been the top performer on the Stockholm Stock Exchange over the past 10 years. Royal Ahold in the Netherlands, Home Depot and Wal-Mart in the United States, Carrefour in France and Marks and Spencer in the United Kingdom have generated spectacular returns for their stockholders. How have they done this? The leading retailers through consolidation, global expansion, technology push and innovative formats, among other approaches outlined in Figure 1, have been 'market driving' rather than 'market driven.' They have shaped consumer behavior, transformed the market place, and redefined the rules of engagement with their competitors and suppliers.